An assessment of small-scale users? inclusion in large-scale water user associations of South Africa - Faysse, Nicolas (International Water Management Institute, 2004)
The management of water resources is being transformed in South Africa. All water users, especially the small-scale ones, are now invited to participate in this movement. This report reviews the process of inclusion of small-scale users in the new large-scale Water User Associations (WUA).Considering the difficulties encountered in this process, this report also recommend external monitoring after the transformation of an Irrigation Board into a WUA. This method may also facilitate assessment of the inclusion of small-scale users into catchment management agencies, and water resource management organizations.